THE ROOTS AND THE STRATEGY FOR POVERTY ALLEVIATION IN THE CITY OF AMBON, MOLLUCAS AND IN THE DISTRICT OF BOALEMO, GORONTALO - Eddy Chiljon Papilaya; Basita Ginting Sugihen (Jurnal Penyuluhan, 2006)
Many poverty alleviation programs had been implemented in the past, but only a few made it. In relation to this, the objectives of this study were: (1) to identify the roots of family poverty, (2) to identify factors related to the family poverty, and (3) to formulate a strategy for poverty alleviation. To reach these objectives, 420 poor households were randomly selected from the city of Ambon and the district of Boalemo, Gorontalo Province. They were interviewed from November 2003 through January 2005. The obtained data were analyzed by using the descriptive statistics and the multiple regression procedures. The findings pointed out that: (1) both the urban and the rural poor households lacked in productive and normative behavior, (2) factors related significantly to the welfare of urban poor families were social and political capitals; whereas to the rural poor families were natural, physical, financial, and behavioral capitals as well, and (3) the grand strategy for both urban and rural poverty alleviation should include good governance, capacity building, social capital revitalization, public policy advocacy, social assurance, infrastructure building, community-based economic development, and asset redistribution.